Evaluation: Media Booklet About Education on Prevention of Flour Albus for Teenage Girl - Cahaya Hidayati; Ei Wah Phyu Thet; Phonethipsavanh Nouanthong (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: To develop booklet media that is effective and appropriate to the needs of young women in high schools, in terms of education on preventing vaginal discharge or Flour Albus, with the aim of increasing their knowledge, awareness and reproductive health behavior. Methodology: The research method used is RnD with a 4D design. Defining needs was carried out through questionnaires to determine the needs of student. Design was created based on the results of the definition. Development is carried out by prelevant design and content. Distribution of booklets is direct distribution in schools. Main Findings: The development of a media booklet about Flour Albus prevention education for young women in high schools was validated by experts with results that were suitable for use and had a significant positive impact in increasing students' knowledge about reproductive health problems. The main findings show that the use of the booklet has succeeded in increasing awareness of adolescent girls about the signs and symptoms of Flour Albus, as well as the preventive steps they can take. Novelty/Originality of this study: The novelty of this research is lies in a holistic approach that pays attention to the special needs of adolescent girls in developing booklet media on the prevention of Flour Albus, integrating accurate information with a visually attractive design to increase engagement and understanding of adolescent girls at the high school level.